Prevalence and characteristics of renal artery fibromuscular dysplasia in hypertensive women below 50 years old. (19th September 2019) - Di Monaco, Silvia; Lengelé, Jean‐Philippe; Heenaye, Sheik; Danse, Etienne; Hammer, Frank; Lopez‐Sublet, Marilucy; Toubiana, Laurent; Rabbia, Franco; Persu, Alexandre
Abstract: Background: Renal fibromuscular dysplasia (FMD) is typically diagnosed in young hypertensive women. The 2014 European FMD Consensus recommended screening in all hypertensive women <30 yo. However, the prevalence of renal FMD in young/middle‐aged hypertensive women remains unclear. The aim of this work was to assess the prevalence and characteristics of renal FMD in hypertensive women ≤50 yo. Methods: We retrospectively included all consecutive women aged ≤50 years referred to our Hypertension Unit from 2014 to 2017 and collected standardized information on patient characteristics and screening modalities. Results: Of 1083 incident hypertensive patients, 157 patients fitted with inclusion criteria. The prevalence of renal FMD varied between 3.2% in the whole sample and 7.5% in patients explored by CTA and/or MRA (n = 67). In the subgroup of patients ≤30 yo (n = 32), the corresponding figures were 3.1% and 5.6%. The yearly prevalence of FMD tended to increase over time, in parallel with increased use of CTA/MRA as a first‐line imaging modality. Out of 5 patients with renal FMD, 2 were revascularized and 1 had extra‐renal FMD. Conclusions: The prevalence of renal FMD in young/middle‐aged hypertensive women is probably one order of magnitude higher than previously assumed, in the range of 3%‐8%, depending on imaging modalities. While the diagnosis of FMD does not influence short‐term management in all patients, it may allow close monitoring and prevention of complications of the disease over time. This analysis provides the rationale for a prospective, multicentre study aiming at determining the cost‐effectiveness of systematic screening for renal FMD.